Morganella morganii, a non-negligent opportunistic pathogen. (September 2016) - Liu, Hui; Zhu, Junmin; Hu, Qiwen; Rao, Xiancai
Highlights: The dissemination of M. morganii is wide. The antibiotic-resistant genes carried by M. morganii are increasing. Virulence evolution makes M. morganii an important pathogen. The disease spectrum associated with M. morganii infections is broad. Abstract: Morganella morganii belongs to the tribe Proteeae of the Enterobacteriaceae family. This species is considered as an unusual opportunistic pathogen that mainly causes post-operative wound and urinary tract infections. However, certain clinical M. morganii isolates present resistance to multiple antibiotics by carrying various resistant genes (such as blaNDM-1, and qnrD1 ), thereby posing a serious challenge for clinical infection control. Moreover, virulence evolution makes M. morganii an important pathogen. Accumulated data have demonstrated that M. morganii can cause various infections, such as sepsis, abscess, purple urine bag syndrome, chorioamnionitis, and cellulitis. This bacterium often results in a high mortality rate in patients with some infections. M. morganii is considered as a non-negligent opportunistic pathogen because of the increased levels of resistance and virulence. In this review, we summarized the epidemiology of M. morganii, particularly on its resistance profile and resistant genes, as well as the disease spectrum and risk factors for its infection.